Digital Daily Text Development for Basic Literacy in Pancasila Learning: Pengembangan Teks Harian Digital untuk Literasi Dasar dalam Pembelajaran Pancasila - Kaharu, Sri Silvana; M. Wantu, Sastro; Cuga, Candra (Indonesian Journal of Innovation Studies, 2025)
General Background: Basic literacy is a fundamental component of education, especially in the digital era where students must master reading, writing, and critical thinking. Specific Background: In East Sumalata Regency, many elementary students face challenges in understanding texts and applying Pancasila values due to conventional learning approaches and lack of contextual media. Knowledge Gap: Despite the availability of digital infrastructure, effective media that integrate daily experiences with Pancasila Education to improve literacy remain limited. Aim: This study aims to develop digital-based Daily Text Activity media using the ASSURE model to enhance students' basic literacy in Pancasila Education. Results: Expert validation resulted in a feasibility score of 90%, and classroom implementation showed improvements in reading comprehension, writing responses, and student engagement. Novelty: The media presents contextual daily texts integrated with Pancasila values, supported by interactive elements such as visuals, audio, and collaborative tasks, designed based on students' real-life environments. Implications: The media not only strengthens basic literacy but also fosters character education rooted in local culture. Its effectiveness indicates potential for broader application in schools with similar characteristics, supported by teacher training to optimize the use of digital learning innovations.Highlight : Digital media daily texts enhance students’ basic literacy in Pancasila Education. ASSURE model ensures structured development and effective classroom implementation. Media content is contextual, interactive, and gains strong validation from experts and practitioners. Keywords : Basic Literacy, Digital Learning Media, Pancasila Education, ASSURE Model, Elementary